The economy of the Tagal Murut of Tenom Sabah (East Malaysia): An ethnographic study / Marcus Shapi - Marcus , Shapi (1989)
This Thesis is an empirical study in ethnography of the economic behaviour of the Tagal Murut in Sabah. It is hoped that this analysis and description will contribute to the reliable information of the contemporary Murut. In chapter I, I deal with the Murut economic in specific and the indigenous people in Sabah in general. It also discussed the methodology, theoretical and field condition. I also criticize the writings of European writers about Murut in chapter II. This chapter gives information regarding Kampong Tilis and the social organizations. In chapter III, my focus is on the production activities of the Tagal Murut. A question that I tried to answer here is of the Tagal Murut’s types of economy. Related to this, chapter IV discussed about distribution, sharing and consumption to the people. I have included the social organization in my scope of discussion in order to understand and reanalysis the concept of ‘communalism’ in contrast to ‘individualism’ of the contemporary Murut. This part was discussed in chapter V under economic and society. In chapter VI, I discussed about the Tagal Murut’s future. This chapter deals with the poverty and development of the people. I relation to the poverty, I have employed the idea of capitalist penetration to the rural people, for example, the logging activities and cash crop cultivation and deals with criticism of different idea to the development.